Advanced Wound Care Products: Mechanisms, Efficacy and Safety Considerations - Munchinamane, Anushree Prakasha (Indian Journal of Pharmacy Practice)
The market for advanced wound care products worldwide is valued at $7.1 billion, with an expected 8.3% annual growth rate, the $7.1 billion global market for advanced wound care products is expected to reach $12.5 billion by 2022-25. This market expansion underscores the increasing demand for innovative solutions to address the complexities of chronic and difficult-to-heal wounds. Despite significant advancements in wound care therapies, the intricate mechanisms underlying both normal and abnormal wound healing are not yet fully understood. Creating an optimal host environment is crucial for facilitating effective wound healing across its various phases. This paper explores advanced wound care products, mechanisms, efficacy and safety considerations, highlighting their critical role in improving patient outcomes. The study provides a comprehensive understanding of how modern wound care innovations contribute to enhanced clinical practices and patient care by analyzing these factors.
Keywords: Wound healing; Hydrophilic polymers; Gelatin; Cellulose; Bone Wax; Silicon Gel and Haemostasis